The Scaling-Up of Microfinance in Bangladesh: Determinants, Impact, and Lessons - Zaman, Hassan (World Bank, Washington, D.C., 2013)
The microfinance industry in Bangladesh currently provides access to credit to around 13 million poor households. The author describes the factors that led to the scaling-up of micro-credit in Bangladesh, the impact this has had on the poor, future challenges in Bangladesh, and possible lessons for other countries. The consensus in the literature is that micro-credit plays a significant role in reducing household vulnerability to a number of risks and that it contributes to improving social indicators. The author argues that strategic donor investments in a handful of well-managed institutions that offer a simple, easily replicable financial product could lead to large gains in access to finance for the poor. However, this approach could sacrifice other objectives of financial sector development, such as product and institutional diversity, which could be promoted after the initial expansion has taken place. Governments can also have a crucial role in promoting access to microfinance by ensuring macroeconomic stability, enforcing a simple regulatory structure, and developing communications networks that reduce transaction costs. Another lesson is that while visionary leadership cannot simply be franchised, the internal management systems that led to the scaling-up can be replicated in other settings.